Edible kefiran films as vehicle for probiotic microorganisms - Piermaria, Judith Araceli (2015)
In the presented work, we have developed edible kefiran films containing Lactobacillus plantarum CIDCA 8327 and Kluyveromyces marxianus CIDCA 8154. Thickness, moisture content and optical properties of films were not altered by the incorporation of microorganisms. During the film obtaining, lactobacillus concentration decreased one logarithmic cycle and no loss on yeast viability was detected. Both microorganisms included in glycerol plasticized kefiran films successfully maintained their viability during storage. After 35 days at 20°°C L. plantarum viability decreased less than 1.3 logarithmic cycles and K. marxianus 0.7 logarithmic cycles. The high susceptibility of free cells of lactobacilli to acid was slightly diminished by the inclusion in the kefiran matrix. Inclusion of K. marxianus CIDCA 8154 significantly improved their survival to the sequential acid-bile treatment (36.3%) compared with the corresponding free cells (8.7%). The obtained edible kefiran films have great potential as an alternative way for probiotic delivery. Industrial relevance The edible kefiran films containing probiotics presented in this manuscript are interesting matrices for probiotic administration since the neutral polysaccharide kefiran, produced by lactic acid bacteria, has health-promoting properties itself. Films can be obtained simply and inexpensively. They are transparent, thin and have good mechanical properties among those constituted by biomacromolecules. Likewise, kefiran films can preserve the viability of probiotics in non-refrigerated conditions.